2017
DOI: 10.1098/rstb.2016.0089
|View full text |Cite
|
Sign up to set email alerts
|

Host allometry influences the evolution of parasite host-generalism: theory and meta-analysis

Abstract: Parasites vary widely in the diversity of hosts they infect: some parasite species are specialists—infecting just a single host species, while others are generalists, capable of infecting many. Understanding the factors that drive parasite host-generalism is of basic biological interest, but also directly relevant to predicting disease emergence in new host species, identifying parasites that are likely to have unidentified additional hosts, and assessing transmission risk. Here, we use mathematical models to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…For parasites in particular, the host body size constitutes another crucial variable influencing their ecology and evolution (Guégan et al 1992;Walker et al 2017). Host body size has long been considered a determinant of parasite species richness, although it generally explains only a portion of the interspecific variance in the numbers of parasite species infecting different host species (Guégan et al 1992;Poulin 2004a;Valtonen et al 2010;Poulin and Leung 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For parasites in particular, the host body size constitutes another crucial variable influencing their ecology and evolution (Guégan et al 1992;Walker et al 2017). Host body size has long been considered a determinant of parasite species richness, although it generally explains only a portion of the interspecific variance in the numbers of parasite species infecting different host species (Guégan et al 1992;Poulin 2004a;Valtonen et al 2010;Poulin and Leung 2011).…”
Section: Discussionmentioning
confidence: 99%
“…variation in pathogen load and stage of infection in the infectious hosts, release and survival of infective stages in the environment, susceptibility and subsequent establishment of the infecting pathogen load in the recipient host). An additional point relating to this, again raised by several of the authors [1,3,7,11,13,14], is how hard it can be to estimate transmission rates in the field. However, considering each step explicitly may help the quantification process, enabling different techniques to be used to estimate the different components, and provide clarification about which specific aspects need further investigation [11].…”
Section: Overview Of Articles and Emerging Topicsmentioning
confidence: 99%
“…Similar suggestions are also raised by some of the other articles in this issue, both in multi-host [14] and single host [7] contexts. In addition, related to the ecological transmission dynamics of parasites within multi-host communities, is the evolutionary issue of whether parasites should evolve to be host generalists or specialists, and several articles addressed different aspects of this question [2,5,8,13]. A key point emerging from these articles is the importance of host-specific traits and characteristics (e.g.…”
Section: Overview Of Articles and Emerging Topicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependency of trade-offs on environmental conditions also needs to be considered [ 84 ]. Intriguingly, research on microsporidians in mosquitoes has shown that the factors influencing selection on vertical versus horizontal transmission include food availability and whether the parasites are embedded in co-infections [ 85 ].…”
Section: Trade-offs and Transmission Modesmentioning
confidence: 99%